Late Frontal Negativity Discriminates Outcomes and Intentions in Trust-Repayment Behavior - Aspé-Sánchez, Mauricio; Mengotti, Paola; Rumiati, Raffaella; Rodríguez-Sickert, Carlos; Ewer, John; Billeke, Pablo (Frontiers in Psychology, 2020)
Altruism (a costly action that benefits others) and reciprocity (the repayment of acts in kind) differ in that the former expresses preferences about the outcome of a social interaction, whereas the latter requires, in addition, ascribing intentions to others. Interestingly, an individual’s behavior and neurophysiological activity under outcome- versus intention-based interactions has not been compared directly using different endowments in the same subject and during the same session. Here, we used a mixed version of the Dictator and the Investment games, together with electroencephalography, to uncover a subject’s behavior and brain activity when challenged with endowments of different sizes in contexts that call for an altruistic (outcome-based) versus a reciprocal (intention-based) response. We found that subjects displayed positive or negative reciprocity (reciprocal responses greater or smaller than that for altruism, respectively) depending on the amount of trust they received. Furthermore, a subject’s late frontal negativity differed between conditions, predicting responses to trust in intentions-based trials. Finally, structures related with mentalizing and cognitive control were the cortical sources of this activity. Thus, our work disentangles the behavioral components present in the repayment of trust, and sheds light on the neural activity underlying the integration of outcomes and perceived intentions in human economic interactions.